Factors of Excellence among Science Proficient University Students - B. Lacambra , Marisa (International Journal of Psychosocial Rehabilitation, 2020)
This study is a qualitative research that focused on the factors of excellence among Science proficient university students. The main objective of this study is to investigate intrinsic as well as extrinsic factors and strategies contributing towards excellent performance of the participants in Science. It is acknowledged that excellence in science learning does not rely only on the way teaching is carried out but also on the other factors such as students’ ability, mathematical and language proficiency, learning strategies and the right attitude toward science learning and others. Nonetheless, little do we know about the extent to which the mentioned factors contribute towards students’ proficiency in science. Through in-depth interviews with the participants who are 20 college students of Cagayan State University at Aparri, the researcher listed several factors that influence excellence among science proficient university students. The results of this study, can be used as a paradigm in crafting a quantitative research that will validate the result. Information pertaining to the factors of excellence can be used to develop a comprehensive inventory that will help assess students’ potential to excel in science.